(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The challenge of bullying among youths engaging in various types of sport is an area that has gained significance in recent areas. The objective of this research is to present an analysis of the extent of bullying in youth sport, the interrelationship of factors contributing to the issue, actions taken to address it, and its outcome. To realize the purpose of the study, a qualitative research approach has been taken. Scientific literature has been reviewed to present an analysis of the theoretical aspects surrounding bullying in youth sports. To facilitate the empirical study, data was gathered from ten organized sportspeople, representing individuals and sports teams of youth sportsmen and women. A semi-structured interview approach was adopted to facilitate data collection. Data analysis was conducted using conceptual content analysis. The processing of data was conducted from within the social group using the emic perspective of the subject as well as using the observer’s perspective. The results of the study indicated three major categories of consequences generated as an outcome of youth bullying in sport: intolerable behavior, the contexts under which bullying takes place, and the severity of the consequences. The analysis of results showcased the nature of bullying, its causes, and outcomes in terms of affecting youth sport participation, career prospects in the sport, and their overall psychological well-being. Findings of the study established that the causes and effects of bullying in youth sport are complex and interrelated; thus, there is a need to examine the deep-rooted, flawed culture in sports that creates a possibility for bullying to take place.